Constraining orientation statistics of ice crystals in clouds with observations from deep space - Kostinski, Alexander; Marshak, Alexander; Várnai, Tamás (Frontiers in Remote Sensing, 2026)
Ice crystals in clouds are often modeled as chaotically oriented despite frequent in situ and remote observations of horizontally oriented crystals. Zenith-pointing ground-based and nadir-pointing space-borne lidars often encounter intense specular reflections (glints), attributed to horizontally oriented particles (HOPs). When the size and shape of these ice crystals are just right, they appear to fall in precisely horizontal orientation with remarkable accuracy. Here, we attempt to constrain the relative contributions, wobbling amplitudes, and sizes of HOPs. Although there is an extensive literature on the topic, our discussion renders orientation randomness more precise and includes several additional considerations: (i) deep space optics of the Earth polychromatic imaging camera (EPIC)/Deep Space Climate Observatory (DSCOVR) observations of angular sizes for cloud glints are brought to bear on the problem; (ii) exponential decay of glint reflectance with angles is observed; (iii) a dimensionless moment of inertia constraint is considered to further constrain sizes; (iv) the dependence of air kinematic viscosity ν is introduced into the argument in tandem with the one on the Reynolds number.